Unearthing Perspectives: Exploring the views of heritage professionals and hobbyists on the current state of metal detecting in Estonia - Tuuli Kurisoo; Maria Smirnova (Internet Archaeology)
This article presents the results of an online survey that explores the views of Estonian heritage professionals and hobbyists on the current state of metal detecting, which has become a popular activity. The hobby is fairly well regulated by law, and both the state and the hobbyists have clear obligations. We asked how local archaeologists and metal detectorists perceive the status quo, what they find positive and negative, and what they would like to see changed. While the majority of the professional archaeologists could point to several positive aspects (e.g. new information, finds), they were clearly concerned about the impact of metal detecting and the capacity of the National Heritage Board to manage the current system. Hobbyists appreciated direct communication with the state, feedback and mandatory training, but were frustrated by the slow pace of feedback, burdensome legislation and mediocre digital solutions. The Estonian archaeological community is small and accustomed to the role of experts. Metal detecting is more of an individual hobby, still in its early stages of development. Similar to several other studies, we believe that better cooperation would help both these stakeholders to perceive archaeology as a common resource that can be used in different ways, but with a shared sense of responsibility.